2022
DOI: 10.1021/acscatal.1c06045
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation of Methane on IrO2(110) Films Investigated Using Ambient-Pressure X-ray Photoelectron Spectroscopy

Abstract: The catalytic oxidation of CH4 over IrO2(110) films grown on Ir(100) was investigated using ambient-pressure X-ray photoelectron spectroscopy (AP-XPS) at total pressures near 1 Torr. The IrO2(110) films undergo negligible reduction during catalytic CH4 oxidation in reactant mixtures with as much as 95% CH4 and temperatures from ca. 500–650 K, demonstrating that IrO2(110) can catalyze the oxidation of CH4 over a wide range of temperatures and mixture compositions. High coverages of OH groups and oxidized C-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(61 citation statements)
references
References 51 publications
8
52
1
Order By: Relevance
“…Surface Ir atoms of adsorbate-free regions of Ir(100) produce a peak at 60.3 eV 22,27 which becomes more evident in the Ir 4f spectrum acquired at 650 K. These spectra resemble that obtained from a reference Ir(100) surface covered with chemisorbed O atoms (Figure S6). For comparison, the Ir 4f 17 Representative O 1s and C 1s spectra acquired from IrO 2 (110) during CH 4 oxidation are shown in Figure 3, mainly for comparison with similar results obtained from Ir(100) (shown below). The O 1s spectra collected from IrO 2 (110) exhibit prominent peaks from surface HO br , HO ot , and CO x species (Figure 3a), with the O 1s peak from CO x surface species decreasing as the temperature is increased from 500 to 650 K while that for HO ot groups concurrently increases.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…Surface Ir atoms of adsorbate-free regions of Ir(100) produce a peak at 60.3 eV 22,27 which becomes more evident in the Ir 4f spectrum acquired at 650 K. These spectra resemble that obtained from a reference Ir(100) surface covered with chemisorbed O atoms (Figure S6). For comparison, the Ir 4f 17 Representative O 1s and C 1s spectra acquired from IrO 2 (110) during CH 4 oxidation are shown in Figure 3, mainly for comparison with similar results obtained from Ir(100) (shown below). The O 1s spectra collected from IrO 2 (110) exhibit prominent peaks from surface HO br , HO ot , and CO x species (Figure 3a), with the O 1s peak from CO x surface species decreasing as the temperature is increased from 500 to 650 K while that for HO ot groups concurrently increases.…”
Section: Resultssupporting
confidence: 52%
“…Details of the experimental procedures have been reported previously and are summarized in the Supporting Information. 17,22,27 Briefly, Ir 4f, O 1s, and C 1s XPS spectra were acquired after stabilizing a gas mixture with 0.1 Torr of O 2 and 0.8 Torr of CH 4 at a sample temperature of ∼300 K and then heating in a stepwise manner from 500 to 650 K.…”
Section: ■ Experimental Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…74,75 But methane is completely oxidized to CO 2 and H 2 O. 76,77 In this study, we only considered a single metal doping and a single oxygen vacancy which is very active for methane adsorption. Cheng et al studied the adsorption and dissociation of methane on ferric oxide oxygen carriers and they found that the activation barrier of C-H decreased when the surface oxygen vacancy concentration was increased from 0%-2.67%.…”
Section: Methane Activationmentioning
confidence: 99%